2014
DOI: 10.1002/acn3.141
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting drug efflux transporters improves efficacy of ALS therapeutics

Abstract: ObjectiveResearch identified promising therapeutics in cell models of Amyotrophic Lateral Sclerosis (ALS), but there is limited progress translating effective treatments to animal models and patients, and ALS remains a disease with no effective treatment. One explanation stems from an acquired pharmacoresistance driven by the drug efflux transporters P-glycoprotein (P-gp) and breast cancer-resistant protein (BCRP), which we have shown are selectively upregulated at the blood-brain and spinal cord barrier (BBB/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
88
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 37 publications
1
88
1
Order By: Relevance
“…Recently, it was shown that the amyotrophic lateral sclerosis (ALS) drug riluzole has increased efficacy in an animal model of familial ALS when co-administered with an ABC transporter inhibitor elacridar (Jablonski et al, 2014). Additionally, co-administration of tariquidar with the anti-seizure drug pentobarbital improves anti-epileptic activity in previously drug resistant rats (Brandt et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that the amyotrophic lateral sclerosis (ALS) drug riluzole has increased efficacy in an animal model of familial ALS when co-administered with an ABC transporter inhibitor elacridar (Jablonski et al, 2014). Additionally, co-administration of tariquidar with the anti-seizure drug pentobarbital improves anti-epileptic activity in previously drug resistant rats (Brandt et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A likely culprit underlying the limited effectiveness of riluzole, the only FDA-approved drug for ALS treatment, is the multidrug efflux transporter ABCB1 or P-glycoprotein (P-gp) (Jablonski et al, 2015; Jablonski et al, 2014). P-gp is a membrane-bound protein that works to expel substances out of cells, and is expressed on the apical membrane (blood side) of endothelial cells, which comprise the functional core of the blood-brain barrier (BBB) and blood spinal cord barrier (BSCB) (Abbott et al, 2010; Wong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These results, together with evidence that riluzole is a P-gp substrate (Milane et al, 2007), suggested that riluzole’s limited efficacy could, at least partially, result from P-gp driven pharmacoresistance that develops over the course of the disease. In a recent proof-of-principle study using SOD1-G93A ALS mice, we showed that co-administration of elacridar, a selective P-gp inhibitor, increased riluzole therapeutic efficacy (Jablonski et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the only current FDA-approved drug for ALS management, riluzole, is suggested to be a P-gp and BCRP substrate [16, 18, 19]. ALS-induced P-gp upregulation could further restrict riluzole permeability across CNS barriers and reduce its concentration at neuronal target sites, thereby lowering its therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Riluzole is the only FDA-approved ALS drug in the clinic, yet it only modestly slows ALS progression during early disease stages in some patients and does not halt or reverse ALS [6]. Since riluzole is a substrate for two ABC xenobiotic efflux transporters, P-gp and BCRP, the full therapeutic efficacy of riluzole in the CNS could be limited by these efflux transporters at the BBB and BSCB [16, 18, 19]. Recent in vivo studies using mouse models of ALS showed that P-gp and BCRP transport activity and expression were induced in CNS barriers during the late stage of disease progression [15, 17].…”
Section: Introductionmentioning
confidence: 99%